Ion channel and lipid scramblase activity associated with expression of TMEM16F/ANO6 isoforms. (27th July 2015) - Scudieri, Paolo; Caci, Emanuela; Venturini, Arianna; Sondo, Elvira; Pianigiani, Giulia; Marchetti, Carla; Ravazzolo, Roberto; Pagani, Franco; Galietta, Luis J. V.
Abstract : Key points: TMEM16F is a membrane protein with possible dual function as an ion channel and a phospholipid scramblase. The properties of ion channels associated with TMEM16F and the link between ion channel and scramblase activity are a matter of debate. We studied the properties of four isoforms of TMEM16F generated by alternative splicing. Upregulation of three TMEM16F isoforms or silencing of endogenous TMEM16F increased and decreased, respectively, both scramblase and channel activities. Introduction of an activating mutation in TMEM16F sequence caused a marked increase in phosphatidylserine scrambling and in ion transport indicating direct involvement of the protein in both functions. Abstract: TMEM16F, also known as ANO6, is a membrane protein that has been associated with phospholipid scramblase and ion channel activity. However, the characteristics of TMEM16F‐dependent channels, particularly the ion selectivity, are a matter of debate. Furthermore, the direct involvement of TMEM16F in phospholipid scrambling has been questioned. We studied the properties of different TMEM16F variants generated by alternative splicing. Using whole‐cell patch‐clamp recordings, we found that V1, V2 and V5 variants generated membrane currents activated by very high (micromolar) intracellular Ca 2+ concentrations and positive membrane potentials. These variants showed different degrees of Ca 2+ sensitivity and kinetics of activation but similar ion permeability, characterized by a slight selectivity for Cl − over Na + . A fourth variant (V3) showing a unique carboxy‐terminus was devoid of activity, in agreement with its intracellular localization. We also measured scramblase activity using the binding of annexin V to detect phosphatidylserine on the cell surface. V1, V2 and V5 variants were associated with calcium‐dependent phosphatidylserine externalization. Interestingly, introduction of an activating mutation, D409G, produced a marked increase in the apparent Ca 2+ sensitivity of TMEM16F‐dependent channels. In parallel, this mutation also enhanced the extent of phosphatidylserine externalization that occurred even under resting conditions. These results support the conclusion that TMEM16F proteins are directly involved in dual activity, as a phospholipid scramblase and as an ion channel. Abstract :